Associations between Sjogren syndrome and psychiatric disorders in European populations: a 2-sample bidirectional Mendelian randomization study - Pan, Lingai; Zhou, Guangpeng; Wei, Guocui; Zhao, Qian; Wang, Yanping; Chen, Qianlan; Xiao, Qing; Song, Yujie; Liang, Xiangui; Zou, Zhili; Li, Xiuxia; Xiong, Xuan (Frontiers in Psychiatry, 2024)
Background: Psychiatric disorders, such as major depressive disorder (MDD), anxiety disorder (AD), bipolar disorder (BD), and schizophrenia (SCZ), are disturbances in brain activity that lead to disorders of cognition, behavior, and emotion regulation.Among Sjogren syndrome (SS) patients, psychiatric disorders are more prevalent than in the general population. Identifying associated risk factors can provide new evidence for clinical diagnosis and treatment. Methods: We selected genetic instruments based on published genome-wide association studies (GWASs) to determine predisposition. Then, we conducted a 2sample bidirectional Mendelian randomization (MR) analysis to explore the potential causal associations between SS and four major psychiatric disorders. The primary analysis was performed using MR with the inverse-variance weighted method.Confirmation was achieved through Steiger filtering and testing to determine the causal direction. Sensitivity analyses were conducted using MR-Egger, MR-PRESSO， and "leave-one-out" method methods.Results: Our study showed that SS was linked to BD and SCZ, indicating that individuals with SS may have a reduced risk of developing BD (IVW: OR = 0.940, P=0.014) and SCZ (IVW: OR = 0.854, P=1.47*10-4), while there was no causal relationship between SS and MDD or AD. MR-Egger regression shows no evidence of pleiotropy (BD: intercept = 0.007, p = 0.774; SCZ: intercept = 0.051, p = 0.209). The same as the MR-PRESSO analysis (BD: global test p = 1.000; SCZ: global test p = 0.160). However, the results from the leave-one-out analysis demonstrated instability. Specifically, after excluding SNP rs3117581, the effects on BD and SCZ were found to be non-significant, suggesting the potential influence of unrecognized confounding factors. The results of the reverse MR show that four major psychiatric disorders had no causal effects on SS.Conclusions: Our research findings demonstrate a causal relationship between SS and SCZ, as well as between SS and BD. There are no causal effects between the four major psychiatric disorders and SS. These findings suggest that SS may have the potential to reduce the risk of both psychiatric disorders. This study provides new insight for their prevention and treatment.